2016
DOI: 10.1155/2016/6072909
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Persistent Lactic Acidosis in the ICU: Glycogenic Hepatopathy and Mauriac Syndrome

Abstract: Mauriac syndrome is a rare disorder that can present with the single feature of glycogenic hepatopathy in children and adults with poorly controlled diabetes mellitus. An often underrecognized finding of glycogenic hepatopathy is lactic acidosis and hyperlactatemia. Primary treatment of glycogenic hepatopathy is improved long-term blood glucose control. Resolution of symptoms and hepatomegaly will occur with improvement in hemoglobin A1C. We present here a case of a young adult female presenting to the intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…In a case-control study by Mukewar et al[ 46 ] analyzing 36 patients with T1DM, more than half of patients with GH had recurrent episodes of DKA, and these patients had higher levels of HbA1c than patients with TIDM without GH. Patients with GH could have elevated levels of plasma lactate, with or without the presence of a DKA episode, although the mechanism is still poorly understood[ 35 , 45 ]. In a retrospective review by Fitzpatrick of 31 patients with Mauriac syndrome, almost half the patients had elevated lactic acid level despite no signs of DKA[ 45 ].…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case-control study by Mukewar et al[ 46 ] analyzing 36 patients with T1DM, more than half of patients with GH had recurrent episodes of DKA, and these patients had higher levels of HbA1c than patients with TIDM without GH. Patients with GH could have elevated levels of plasma lactate, with or without the presence of a DKA episode, although the mechanism is still poorly understood[ 35 , 45 ]. In a retrospective review by Fitzpatrick of 31 patients with Mauriac syndrome, almost half the patients had elevated lactic acid level despite no signs of DKA[ 45 ].…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…One of the proposed theories is that a reduction in gluconeogenesis in the liver may raise lactate levels in the body. Therefore, lactic acidosis could be secondary to reduced gluconeogenesis and a lack of conversion of pyruvate to glucose[ 35 ].…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…GH is a rare and underreported complication of poorly controlled T1DM, although occasionally this condition can also be observed in patients with type 2 diabetes mellitus. Indeed, up to now ~130 cases with GH have been published in the PubMed database 15–26. In general, GH is considered a benign and reversible disease but recent studies have also reported varying degree of fibrosis including bridging fibrosis in a minority of patients 2 18–21.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Canadian authors have linked the occurrence of glycogenic hepatopathy with lactic acidosis [25]. These authors claim that further research is required to explain the pathophysiology of lactic acidosis in glycogenic hepatopathy.…”
Section: Discussionmentioning
confidence: 99%